CRITICAL ENGLISH READING RESULTS USING THE STARTING STRATEGY OF GRADE-8 STUDENTS - Poolbangyung, Benjawan; Patamadilok, Sudakarn (Journal of Buddhist Education and Research (JBER), 2022)
The purpose of this research are: 1) compare English critical reading achievement of Grade-8 students’ before and after using START strategy and 2) compare English critical reading achievement of Grade-8 students after using START strategy with 75% criterion. The sample group in this research was 38 Grade-8 students of Thapthan Anusorn School, Uthaithani, the Secondary Educational Service Area Office Uthaithani in the academic year 2/2020 selected by purposive sampling. The research tools were lesson plans in English Critical Reading Course by using START strategy which had quality average at 4.31 and 2) learning achievement test which had difficulty (p) from 0.56 - 0.78, power of discriminant (r) from 0.40 - 0.77, reliability at 0.93 and tested hypothesis with t-test of independent group and one group. The research result finds that: 1. Learning the achievement of the Grade-8 students after using the START strategy in was significantly higher than before using the START strategy at the .05 level. 2. Their learning achievement of Grade-8 students after using START strategy was higher than 75% criterion 76.23 and the required standard 75/75.